2014
DOI: 10.1097/meg.0000000000000203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of mean platelet volume and red blood cell distribution width to platelet ratio for predicting the severity of hepatic fibrosis in chronic hepatitis B virus patients

Abstract: MPV and RDW values are significantly higher in hepatitis B virus-infected patients, associated with severity, and can be defined as independent predicting factors in hepatic fibrosis. Further studies are required to determine the associations between MPV and the severity of fibrosis in hepatitis B patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 18 publications
5
69
1
2
Order By: Relevance
“…While there was no significiant difference in MPV levels between acute hepatitis B patients and healthy controls, higher MPV values in chronic hepatitis B patients compared with acute hepatitis B patients or healthy controls have been indicated [8,20]. Additionally, it has been reported that MPV can be defined as independent predicting factor in hepatic fibrosis [8].…”
Section: Mpv and Viral Hepatitismentioning
confidence: 99%
See 2 more Smart Citations
“…While there was no significiant difference in MPV levels between acute hepatitis B patients and healthy controls, higher MPV values in chronic hepatitis B patients compared with acute hepatitis B patients or healthy controls have been indicated [8,20]. Additionally, it has been reported that MPV can be defined as independent predicting factor in hepatic fibrosis [8].…”
Section: Mpv and Viral Hepatitismentioning
confidence: 99%
“…Aside from their function in haemostasis, platelets have also a crurical role in the inflammatory response, and also their counts may change in parallel with the severity of infections [1][2][3][4][5][6][7][8][9][10][11]. In addition to changes in platelet counts during infections, platelet sizes can be altered by some factors such as platelet formation from megakaryocytes in response to thrombocytopenia or the release of platelet granules due to the activation of platelets [1][2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They declared that plateletderived indices may play a critical role in monitoring liver fibrosis and cirrhosis progression. Karagoz et al (13) found significantly high MPV and RDW values in HBV infected patients, and they declared that these parameters could be used in determining liver damage. In our study, there was no difference between the groups in terms of MPV and PDW values.…”
Section: Discussionmentioning
confidence: 99%
“…It is used in predicting the cause of anemia (12). New studies have declared that elevation of RDW values is associated with high mortality risk in different patient groups (13).…”
Section: Introductionmentioning
confidence: 99%